Photography, memory and nostalgia - Im, Yung-Ho (Javnost (Ljubljana), 2007)
Based on the photographs of Ki-chan Kim, this essay examines how the tradition of documentary photography in Korea evolved in terms of subject, style, and ways of seeing. It emerged as a humanistic response to the harsh social reality of the 1940s in an oppressive political atmosphere for photographers dealing with socially sensitive subjects. Hence, a compromise between roles of the arts and social muckraking characterised the evolving documentary tradition. In documenting the back streets of Seoul, Kim tends to reduce a subject with broad social implications to an introspective story of personal memory, thus representing the Korean documentary tradition.
Keywords: Južna Koreja; družbene razmere; politične razmere; dokumentarna fotografija; fotografi; List of photographers